How economic crises damage potential output: evidence from the Great Recession - Dovern, Jonas; Zuber, Christopher (Journal of macroeconomics, 2020)
Economic crises lead to lower potential output (PO) estimates, but little is known about which components of PO are revised. Our paper answers the questions of how much, how fast, and how persistently estimates of the capital stock, of trend labor, and of trend total factor productivity are revised downwards after major economic crises. It shows that revisions to different components of PO contributed equally to the substantial overall decline in estimated PO levels. Revisions of trend labor are predominantly driven by revisions of the NAWRU. The heterogeneity of revisions across EU countries after the Great Recession is large, suggesting that different policies are needed to bring countries back to their previous growth paths.
Gesehen am 27.11.2020